Rezension von: Hagdorn, Hans u.a. (Hrsg.), Muschelkalk - Seegis, Dieter B. (Württembergisch Franken, 1995)
Hans Hagdorn, Theo Simon, Joachim Szule (Hrsgg.), Muschelkalk. A Field Guide, Korb (Goldschneck) 1991. 80S., 78 Abb.